The Effectiveness of Using Humorous Stories to Improve Students’ Reading Interest (Karya Ilmiah Mahasiswa (KIMA), 2026)
The purposes of this research were to discover the effectiveness of using humorous stories in improving students’ reading interest and to investigate students’ obstacle in using humorous stories in improving students’ reading interest. This research used a quantitative method with a group of pre-test and post-test design. This research was conducted at SMP Islam Darul Hikmah Makassar with the sample of  the 29 seventh grade students. To collect data, two types of research instruments were employed, a test and  an instrument. The research results show that the use of humorous stories significantly improve the students’ reading interest. The value of the pre-test is 1270 while the post-test is 2250. Then, the average of the pre-test and post-test is 43.79 and 77.58 respectively. This indicates that there is an increasing 77% from the pre-test to the post-test. In conclusion, the use of humorous stories is effective in improving students’ reading interest.